ANALISIS YURIDIS DAMPAK INFLASI TERHADAP PEKERJA BERDASARKAN UNDANG-UNDANG KETENAGAKERJAAN - Afton, Pramudhya; Ukas, Ukas (LPPM Universitas Putera Batam, 2023)
The impact of inflation is often used as an indicator of differences of opinion regarding human resources and sources of employment, between groups of workers, and between regions. This study aims to provide a juridical analysis of the effect of inflation on labor, unemployment, and the poor on inflation and employment inequality. This study uses research data based on labor law and data analysis is carried out with this juridical framework based on law number 13 of 2003 and article 7 of law number 23 of 1999 showing the impact of inflation on human resources and sources of labor, unemployment and the poor affect development inequality in cities affected by inflation.